FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU DI MASA PANDEMI COVID-19 DAN KELENGKAPAN IMUNISASI DASAR PADA BAYI 9-13 BULAN DI PUSKESMAS KOYA KABUPATEN MINAHASA - Eireine Maria Pandoh; Adrian Umboh; Novie Rampengan (Stikes Syedza Saintika Padang, 2022)
Global Alliance for Vaccine and Immunization (GAVI), World Health Organization (WHO), and United Nations International Children Emergency Fundy (UNICEF) reported that 80 million children aged less than 1 year are at risk of suffering from diseases that can be prevented by giving immunizations (PD3I) due to disruption of routine immunization services in the midst of the COVID-19 pandemic. The purpose of this study was to determine the relationship between these factors.Related to maternal behavior during the COVID-19 pandemic and completeness of basic immunization for infants 9-13 months at the Koya Health Center in Minahasa Regency. The sample obtained amounted to 145 respondents with purposeve sampling technique. The activety began by signing the agreement, and continued with interviews, then filling out the questionnaire.Design This research is analytic observational, with aapproach cross sectional. Data analysis used univariate analysis, bivariate analysis withtest Chi-square, and multivariate with logistic regression test. The results of thetest chi square of each variable found the p value of education (p = 0.01), work (p = 0.193), knowledge (p = 0.01), attitude (p = 0.01), family support (p = 0.01) p=0.01), attitude of health workers (p=0.02). The results of the logistic regression test showed that the variable with the highest OR value was family support (OR = 2.45). Conclusion: there is a relationship between education, knowledge, attitudes, family support, attitudes of health workers to the completeness of basic immunization, and the factor most related to the completeness of basic immunization is family support.